2016
DOI: 10.1007/s12012-016-9392-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Emulsion Inhibits Apoptosis Induced by a Toxic Dose of Verapamil via the Delta-Opioid Receptor in H9c2 Rat Cardiomyoblasts

Abstract: The goals of this study were to investigate the effects of lipid emulsion (LE) on apoptosis induced by a toxic dose of verapamil in H9c2 cells and to elucidate the associated cellular mechanism. The effects of LE alone and combined with an inhibitor on the decreases in cell counts and viability induced by verapamil and diltiazem were examined using the MTT assay. The effects of verapamil alone, combined LE and verapamil treatment, and combined inhibitor, LE and verapamil treatment on cleaved caspase-3, caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…The mechanism associated with the apoptosis observed in doxorubicin-induced cardiotoxicity has been extensively investigated, and multiple pathways are known to be involved in apoptotic cell death [ 16 , 26 ]. Lipid emulsion reversed the cell viability decrease induced by bupivacaine or verapamil in H9c2 cells [ 13 , 14 ]. Similar to these previous reports, the results presented herein demonstrated that lipid emulsion attenuated the decreased cell viability induced by doxorubicin, as determined by the MTT assay ( Figure 1 B) [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanism associated with the apoptosis observed in doxorubicin-induced cardiotoxicity has been extensively investigated, and multiple pathways are known to be involved in apoptotic cell death [ 16 , 26 ]. Lipid emulsion reversed the cell viability decrease induced by bupivacaine or verapamil in H9c2 cells [ 13 , 14 ]. Similar to these previous reports, the results presented herein demonstrated that lipid emulsion attenuated the decreased cell viability induced by doxorubicin, as determined by the MTT assay ( Figure 1 B) [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid emulsion reversed the cell viability decrease induced by bupivacaine or verapamil in H9c2 cells [ 13 , 14 ]. Similar to these previous reports, the results presented herein demonstrated that lipid emulsion attenuated the decreased cell viability induced by doxorubicin, as determined by the MTT assay ( Figure 1 B) [ 13 , 14 ]. α- and γ-linolenic acid, which are long-chain fatty acids, counteract the cardiotoxicity of doxorubicin [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations